2022
DOI: 10.1039/d1rp00301a
|View full text |Cite
|
Sign up to set email alerts
|

Considering alternative reaction mechanisms: students’ use of multiple representations to reason about mechanisms for a writing-to-learn assignment

Abstract: Organic reaction mechanisms are often represented by the electron-pushing formalism and reaction coordinate diagrams. These representations pose a challenge to students because valuable information is encoded within each representation, and students must know how to reason about mechanisms using both. Hence, it is important to understand whether and how students consider these two representations when reasoning about reaction mechanisms. We have collected responses to a writing-to-learn assignment administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…Prior work has shown a disparity between how electrophiles and nucleophiles are identified and described in various contexts with a particular reliance on explicit structural features (Bhattacharyya and Bodner, 2005;Strickland et al, 2010;Bhattacharyya, 2014;Bretz, 2015, 2016;Graulich, 2015;Akkuzu and Uyulgan, 2016;Putica and Trivic, 2016;Galloway et al, 2017;Caspari et al, 2018a;Dood et al, 2020a;Watts et al, 2020Watts et al, , 2022Dood and Watts, 2022b). Bretz (2015, 2016) found that learners were more apt at identifying and providing examples of electrophiles and nucleophiles when charge was explicit: for example, the positive carbon in a carbocation species or the negatively charged oxygen of an alkoxide.…”
Section: Electrophiles and Nucleophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has shown a disparity between how electrophiles and nucleophiles are identified and described in various contexts with a particular reliance on explicit structural features (Bhattacharyya and Bodner, 2005;Strickland et al, 2010;Bhattacharyya, 2014;Bretz, 2015, 2016;Graulich, 2015;Akkuzu and Uyulgan, 2016;Putica and Trivic, 2016;Galloway et al, 2017;Caspari et al, 2018a;Dood et al, 2020a;Watts et al, 2020Watts et al, , 2022Dood and Watts, 2022b). Bretz (2015, 2016) found that learners were more apt at identifying and providing examples of electrophiles and nucleophiles when charge was explicit: for example, the positive carbon in a carbocation species or the negatively charged oxygen of an alkoxide.…”
Section: Electrophiles and Nucleophilesmentioning
confidence: 99%
“…At the heart of such difficulty is translating the representational system for chemical structure and reaction mechanisms (i.e., the electron-pushing formalism) into nuanced understandings (often implicit features) of electron deficient and electron sufficient atoms and moieties. While electrophiles and nucleophiles are paired, the research literature suggests that learners have a differential understanding of the two, with more proficiency associated with identifying and describing nucleophiles Bretz, 2015, 2016;Galloway et al, 2017;Caspari, et al, 2018a;Graulich et al, 2019;Watts et al, 2020Watts et al, , 2022. At present, chemistry education researchers in this area have primarily used in-depth interviews to explore learners' understanding of organic chemistry topics.…”
Section: Introductionmentioning
confidence: 99%
“…As Cooper and others have argued, learners must have opportunities to demonstrate and wrestle with any outcome or objective we seek through our instruction (Cooper, 2015;Becker et al, 2016;Stowe and Cooper, 2017;Bode ´et al, 2019;Galloway et al, 2019;Watts et al, 2020Watts et al, , 2022. In other words, if we want learners to ascribe meaning to reaction mechanism drawings, then we must ask learners to communicate that meaning, e.g., through written explanations.…”
Section: Introductionmentioning
confidence: 99%
“…Representational competence refers to ''a set of skills and practices that allow a person to reflectively use a variety of representations or visualizations, singly and together, to think about, communicate, and act on chemical phenomena in terms of underlying, aperceptual physical entities and processes'' (Kozma and Russell, 2005, p. 131). Representational competence has frequently been of interest in chemistry education research (Atkinson et al, 2021;Parobek et al, 2021;Popova and Jones, 2021;To ´thova ´et al, 2021;Watts et al, 2022) and has been considered when evaluating the effect of representations on students' learning (Larkin and Simon, 1987;Hsu and Yang, 2007;Ariasi and Mason, 2014;Enero Upahi and Ramnarain, 2019;Gkitzia et al, 2020).…”
Section: Non-textual Explanationsmentioning
confidence: 99%
“…For chemistry, education research also focuses on specialised forms of representations like symbolic language features of the language of chemistry (Taber, 2015;Liu and Taber, 2016) or mechanistic language features in organic chemistry (Bongers et al, 2019;Watts et al, 2022). Research by Bhattacharyya (2014), Galloway et al (2017) and Graulich and Caspari (2021) outline differences of students' reading and interpretation of mechanistic language in chemistry and spectra are evaluated in terms of reading texts on the tertiary level (Topczewski et al, 2017;Connor et al, 2021).…”
Section: Non-textual Explanationsmentioning
confidence: 99%